Rethinking The Role of Power and Trust in Tourism Planning - Nunkoo, R.; Gursoy, D (Routledge, 2015)
© 2015, Routledge. All rights reserved. Power and trust are two fundamental components of a sustainable and democratic tourism planning process. Yet, tourism research integrating these concepts together has remained virtually silent in the literature. This article adopts Foucault’s theoretical perspectives on power to explain power relationships in tourism at the community level. The discussion suggests that Foucault’s conceptualizations of power, that is, “the omnipresence of power” and “power in (tourism) networks,” are vital for an understanding of the politics of tourism. The article further borrows from the political science literature and emphasizes on trust as another important ingredient of sustainable tourism development. More specifically, the arguments are based on the concept of political trust, conceptualized as citizens’ trust in tourism institutions. The article argues that citizens’ trust in tourism institutions is vital for a democratic tourism planning process. The discussion further suggests that citizens’ power in tourism decision-making and their trust in tourism institutions are vital for gaining their political support for development.